The knowledge economy in Europe: A review of the 2009 EIB Conference in Economics and Finance - Kristian Uppenberg (European Investment Bank (EIB), 2010)
This overview discusses some key findings of the papers presented at the conference and draws some policy conclusions from them in the context of the broader literature. The papers and the wider academic discussion are sorted into three broad groups. The first looks at macroeconomic issues: The measurement of intangible capital and how this affects economic growth (Sections 2-4). The second group analyses the motivations of firms to invest in R&D and the role of public policy in spurring innovation (Section 5). The third group focuses on the financing of innovation (Section 6). Section 7 concludes.
Keywords: 330; knowledge economy; macroeconomics; research and development; innovation; conference proceedings; financing; intellectual capital